Methane reforming over a high temperature stable-NiCoMgOx supported on zirconia-hafnia catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Choudhary, Tushar V. (Chemical Engineering Journal, 2006)
The unusually high temperature stable NiCoMgOx (Ni/Co/Mg: 1:0.2:1.2)/zirconia-hafnia catalyst has been investigated for syngas generation via the catalytic partial oxidation of methane (CPOM), oxidative steam reforming of methane (OSRM) and oxidative CO2 reforming of methane (OCRM) processes. The catalyst, even when calcined at 1400 degrees C for 4 h, showed excellent activity/selectivity for the CPOM, OSRM and the OCRM reactions. On account of its high thermal stability, hot spots in the catalyst bed and/or high temperatures prevailing at the catalyst surface during the oxy-reforming processes would have little or no effect on the catalytic activity/selectivity of the NiCoMgOx/zirconia-hafnia catalyst, thus making the catalyst suitable even for operating under adiabatic conditions. While the selectivity for CO increased considerably with increasing reaction temperature for the CPOM process, the selectivity for H-2 was affected to a much lesser extent. The selectivity for CO and H-2 in the CPOM reaction was found to decrease with increasing space velocity; the H-2 selectivity was however affected to a greater extent. For the OSRM process, the H2O/CH4 ratio profoundly influenced the H-2/CO ratio and the heat of the reaction. Depending on the H2O/CH4 ratio, the OSRM process could be operated in a mildly exothermic, thermoneutral or mildly endothermic mode. The CO2 conversion increased rapidly with increasing OCRM temperature and correspondingly the exothermicity of the OCRM reaction was found to decrease with increasing reaction temperature. At 900 degrees C, the OCRM reaction was mildly exothermic and provided high methane conversion and syngas selectivity. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: high temperature stable catalyst; methane; oxy-dry reforming; oxy-steam reforming; Partial oxidation

Magnesium oxide supported nano-gold: a highly active catalyst for solvent-free oxidation of benzyl alcohol to benzaldehyde by TBHP - Choudhary, Vasant R.; Dumbre, Deepa K. (Catalysis Communications, 2009)
Nano-size gold particles deposited on MgO by the homogeneous deposition- precipitation showed very high catalytic activity with nearly 100% conversion of benzyl alcohol in a short reaction period (0.5 h) and more over showed excellent reusability in the process. Influence of the catalyst support (MgO, CaO, BaO, SrO, Al(2)O(3), Ga(2)O(3) and In(2)O(3)), method of gold deposition, Au loading and catalyst calcination temperature and also that of the reaction conditions (viz. reaction time and temperature) on the benzyl alcohol to benzaldehyde oxidation have been thoroughly investigated. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkaline earth oxides; Benzaldehyde; Benzyl alcohol; Gr.IIIa metal oxides; Oxidation

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation